Pengembangan E-LKPD Berbasis STEM (Science, Technology, Engineering, and Mathematics) Materi Wujud Zat dan Perubahannya untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas IV MI - Joni Alwis; Endang Widi Winarni; Neza Agusdianita (UNIB Press, 2026)
The purpose of this study was to develop a STEM-based E-LKPD product on the states of matter and their changes to improve the cognitive learning outcomes of fourth-grade MI students. This study employed a Research and Development (R&D) approach using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The data collected consisted of quantitative and qualitative data. Quantitative data were obtained from the validation results of material, language, and graphic experts, product trials, as well as effectiveness tests conducted through pretests and posttests. Qualitative data were gathered from interviews, observations, and questionnaires regarding teacher and student responses. The findings revealed that the STEM-based E-LKPD developed in this study was deemed appropriate for use based on evaluations by material, language, and graphic expert validators. Teacher and student responses fell into the very positive category, particularly concerning the appearance and ease of use of the media. Furthermore, the effectiveness test showed an improvement in students’ problem-solving abilities, with an N-Gain score of 0.7108, categorized as quite high. Based on these results, it can be concluded that the STEM-based E-LKPD is effective in improving the cognitive learning outcomes of fourth-grade MI students.